Perencanaan Teknik Penanggulangan Kelongsoran Dengan Menggunakan Konstruksi Retaining Wall (Studi Kasus Jalan Tanjung Selor – Tana Tidung) - Hasrullah, Hasrullah (Jurusan Teknik Sipil, 2018)
Given the contours of the island of Borneo are numerous plateaus, allowing roads to be constructed in mountainous areas or hilly, it can be seen on the streets shaft North Kalimantan namely Tanjung Selor – Tana Tidung road on the path Tanjung Selor – Tana Tidung road there is a level of steepness high whitout made retaining wall can be causing landslides that could be dangerous for road users and surrounding residents. This can occur as a result of soil instability especially when coupled with high rainfall, It is necessary to retaining that handy to withstand the preassures in the soil so that the soil does not move and headed towards the bottom. With the development of science, the more ways you can use to avoid or rectify the land / area avalanche of one of them by making a retaining wall.